Analysis of work activities involved in clearance verification process of decommissioning Fugen Nuclear Power Plant - Yamamoto, Kosuke; Yanagihara, Satoshi (Journal of Nuclear Science and Technology, 2022)
A series of work activities involved in clearance verification process was analyzed from the viewpoint of work efficiency in dismantling turbine facilities at Fugen Nuclear Power Plant. The work activities relating to clearance verification process were divided into four steps: pre-treatment, decontamination, surface monitoring at gate of controlled area for transportation, and clearance monitoring. Of these steps, decontamination required the most manpower expenditure. In addition, pre-decontamination surface monitoring showed that most of the cut pieces were below the detection limit. This corresponds with the fact that most parts of the turbine system were evaluated to have low levels of radioactivity when the plant ceased operation in 2003, and the radioactivity is even lower due to decay since shutdown. The analysis of the clearance verification process indicates the potential effectiveness of reducing or skipping the decontamination efforts for the parts that are known to have low-enough radioactivity. In addition, it is possible to improve the efficiency by only monitoring selected representative samples instead of all units for clearance verification, depending on the degree of contamination. Our analysis revealed that person-hours can be reduced by 37% by using pre-decontamination surface monitoring to make decontamination decision in the case of Fugen decommissioning.